A valuable cardiac magnetic resonance investigation after MINOCA/takotsubo Syndrome: a case report - Snehasis Pradhan; Nedall Zalloum; Gresa Kciku; Hans‐Joachim Trappe (ESC Heart Failure, 2020)
Abstract Myocardial infarction with non‐obstructive coronary arteries is a working diagnosis that includes takotsubo cardiomyopathy/syndrome (TTS). Cardiac magnetic resonance (CMR) is useful for establishing the underlying aetiology of myocardial infarction with non‐obstructive coronary arteries during the acute phase, but its role in follow‐up is less well established. A 35‐year‐old man with several cardiac risk factors presented 3 days after his sister's death with biochemical and clinical features of acute myocardial infarction without coronary artery obstruction on angiography but with diagnostic features of TTS on CMR, including oedema but no late gadolinium enhancement. Subsequent CMR 3 months later revealed left ventricular late gadolinium enhancement suggesting previous acute myocardial infarction. Although the initial diagnosis of TTS was robust according to established criteria, it remained uncertain whether the later ischaemic injury was related to an ischaemic event at presentation or occurred in the intervening period. Nevertheless, CMR may have an extended role in the follow‐up of these patients and may reveal additional, actionable pathology.